Contribuições e limitações das políticas públicas para o fortalecimento das agricultoras: o caso da Organização de Mulheres do Assentamento Tucano (OMAT) em Euclides da Cunha Paulista (SP) - Paula, Larissa Araújo Coutinho de [UNESP] (2015)
Considering the long story of the rural work revendications to the farmland access to a best life conditions and also work conditions, it's deemed and the elaboration of public policies as the answers to those demands. Therefore the aim that carried this research was evaluate how The Food Acquisition Program, The National School Food Program, The Woman National Program for Strengthening Family Farming, The National Documentation of the Rural Worker Woman and The Program Child Benefit are being operated and which results have been generated in the life of the women organization members of the Tucano settlement, in Euclides da Cunha Paulista (SP). It was adopted as a methodological perspective the focus on the settlement families' routine, doing interviews (thematic and oral history) with the leaders of the Association, the other participants of the group, staff of municipal and state public institutions, as well the old female leaderships that used to organize the actions in the camping phase during the struggle for land. It was noticed although there are problems, the policies have positive effect in the women life with a certain rental autonomy, the improvement of the self-esteem, a major awareness of gender relations in a domestic and productive work terms, the return to the studies and the tentative of circulation by the association of common objectives despite of the constants conflicts between men and women and between the women themselves